The Ministry of Reconciliation: Healing the past, truth of the present, hope for the future - Guerrero, Pablo (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2016)
The purpose of these pages is to think about the reconciliation as service, as ministry. A ministry that builds up the Church because it is one of her own actions. A ministry that tries to understand and to promote the Christian community life in a more just and fraternal world. The whole Church is committed to the ministry of reconciliation: a mission which is to recover, assuming and (re) create; a mission that seeks to establish just and human relations; a mission that accompanies the process of forgiveness by the offended, realizing that forgiveness is not identified with reconciliation, it does not solve all the pain, but it part of the process.